Vitamin D receptor BsmI polymorphism may be associated with an decreased osteoporosis risk in South China - An, M.; Song, X-B.; Chen, X-Y. (Cellular and Molecular Biology, 2017)
Although many epidemiology studies have evaluated the correlation between vitamin D receptor (VDR) BsmI polymorphism and osteoporosis, the current results remain inconclusive. This meta-analysis updated and reevaluated the possible association between VDR BsmI polymorphism and osteoporosis in Chinese populations. Studies were identified using PubMed and Chinese databases through December 2016. The associations were assessed with pooled odds ratios (ORs) and 95% confidence intervals (CIs). A total of nine studies with 688 osteoporosis cases and 730 controls were included in this meta-analysis. Overall, no significant association was found between VDR BsmI polymorphism and osteoporosis when all studies in Chinese populations were pooled into this meta-analysis. In subgroup analyses, significantly decreased risk was found in South China (bb vs. BB: OR = 0.22, 95% CI = 0.06-0.76; bb+Bb vs.BB: OR = 0.27, 95% CI = 0.09-0.81). This meta-analysis suggests that VDR BsmI polymorphism may have a protective role against the development of osteoporosis in South China.